Effect of Histone Lysine Methylation on DNA Lesion Reactivity in Nucleosome Core Particles - Yang, Kun (Chem Res Toxicol, 2019)
Lysine methylation is a common posttranslational histone modification that regulates transcription and gene expression. The lysine residues in the histone tail also react with damaged nucleotides in chromatin, including abasic sites and N7-methyl-2'-deoxyguanosine, the major product of DNA methylating agents. Lysine monomethylation transforms the ε-amine into a secondary amine, which could be more nucleophilic and/or basic than the ε-amine in lysine, and therefore more reactive with damaged DNA. The effect of lysine methylation on the reactivity with abasic sites and N7-methyl-2'-deoxyguanosine was examined in nucleosome core particles using a lysine analogue derived from cysteine. ε-Amine methylation increases the rate constant for abasic site reaction within nucleosome core particles. Reactivity at the two positions examined increased less than two-fold. Mechanistic experiments indicate that faster β-elimination from an intermediate iminium ion account for accelerated abasic reactivity. The rate constants for nucleophilic attack (Schiff base/iminium ion formation) by the lysine and methylated analogues are indistinguishable. Similarly, the rate constants describing nucleophilic attack by the lysine and methylated lysine analogues on β-2'-fluoro-N7-methyl-2'-deoxyguanosine to form DNA-protein cross-links are also within experimental error of one another. These data indicate that abasic site containing DNA will be destabilized by lysine methylation. However, these experiments do not indicate that DNA-protein cross-link formation, a recently discovered form of damage resulting from N7-guanine methylation, will be affected by this posttranslational modification.